2019
DOI: 10.1097/phm.0000000000001228
|View full text |Cite
|
Sign up to set email alerts
|

Energy Cost of Slow and Normal Gait Speeds in Low and Normally Functioning Adults

Abstract: Objective Slow walking speed paired with increased energy cost is a strong predictor for mortality and disability in older adults but has yet to be examined in a heterogeneous sample (ie, age, sex, disease status). The aim of this study was to examine energy cost of slow and normal walking speeds among low-and normal-functioning adults. Design Adults aged 20-90 yrs were recruited for this study. Participants completed a 10-m functional walk test at a selfselected normal walking speed and were categorized as lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
(39 reference statements)
1
0
0
Order By: Relevance
“…The results of this study showed that frailty increased the risk of unplanned readmission by 1.5-fold in patients with CHF, which is consistent with the findings of Kojima et al [21]. Patients with frailty have unique characteristics of decreased muscle strength, decreased gait speed and increased gait variability [39], which makes patients with CHF with frailty more likely to fall [40] and indirectly increases the risk of unplanned readmission in patients with CHF. In addition, CHF complicated with frailty had multiple chronic diseases and multiple drug use, increasing the possibility of unplanned readmission [41].…”
Section: Frailty Increases the Risk Of Unplanned Readmission In Patie...supporting
confidence: 88%
“…The results of this study showed that frailty increased the risk of unplanned readmission by 1.5-fold in patients with CHF, which is consistent with the findings of Kojima et al [21]. Patients with frailty have unique characteristics of decreased muscle strength, decreased gait speed and increased gait variability [39], which makes patients with CHF with frailty more likely to fall [40] and indirectly increases the risk of unplanned readmission in patients with CHF. In addition, CHF complicated with frailty had multiple chronic diseases and multiple drug use, increasing the possibility of unplanned readmission [41].…”
Section: Frailty Increases the Risk Of Unplanned Readmission In Patie...supporting
confidence: 88%